Cloud Computing Security Techniques for Enhancing Utilization Efficiency - Jaya,; Kaur, Kiranbir (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides resources or services both in terms of hardware and software using network (typically internet). Physical machines thus can perform operations beyond their capabilities. Cloud provides services including IaaS, PaaS and SaaS. Everything user needs is physically close to them hence extensive use of cloud is on the prospect. As users increases so does security threats. Cloud resources could be the target through application of attacks. Several techniques being suggested and research over to avoid critical consequence of threats. This paper provides comprehensive study of techniques used to enhance security within cloud computing environment. Comparative study also list best possible techniques which can work upon in the future.